Análisis al comercio electrónico en las pequeñas y medianas empresas del sector real en Colombia como herramienta de mercadeo (2017)
In Colombia, according to the data reported to confecámaras and the Registro Único Empresarial (RUES), there are about 2.3 million companies registered in the country under the name of SMEs, which according to figures reported by the Ministry of ICT only 8 % of companies distribute their products through electronic channels. The Colombian Chamber of Electronic Commerce, in a second study of non-face-to-face transactions, reported that Internet financial transactions represented 2.6% of GDP (gross domestic product) in Colombia in 2014, amounting to USD $ 9,961 million distributed in different categories, including payments to government entities as well as state revenue transactions equivalent to 53%, while the remaining 47% consisted of transactions under the B2C modality (business to consumer) in which the following can be mentioned: travel agencies, technology consumption and retail trade.